Metabolomics-based profiling with chemometric approach to identify bioactive compounds in Salacca zalacca fruits extracts and in silico molecular docking - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Alshwyeh, Hussah Abdullah; Al-Mekhlafi, Nabil Ali; Mediani, Ahmed; Ibrahim, Zalikha; Ismail, Nor Hadiani; Kamisah, Yusof (Elseviers, 2021)
Salak (Salacca zalacca) is well-known as snake fruit and it is immensely studied for its antioxidative and antidiabetic active metabolites throughout the southeast Asian countries. However, there are many remaining unidentified metabolites due to very low abundance and natural variation, which need to be further explored. Nowadays mass spectrometry (MS/MS) facilitates the tentative identification of unknown compounds in the crude herbal extracts. This study described the metabolite profiling of hydroalcoholic extracts of S. zalacca analysed by LCQTOF- MS/MS. The 60% ethanolic extract exhibited the highest a-glucosidase inhibition and ferric reducing antioxidant power activities with IC50 of 15.94 mg/mL and 78.13 lg AAE/g, respectively. Multivariate data analysis (MVDA) by an orthogonal partial least-squares (OPLS) algorithm was conducted to correlate the a-glucosidase inhibition activity with the LC- QTOF-MS data. A total of 4 compounds were reported for first time in this fruit and identified based on the molecular mass and fragment ions. LC-QTOF-MS analysis indicated the presence of carexane I, 5-phenoxytetra zol-1-yl)-2,3,5,6-hexahydrofurofuran-3-ethylurea, 3-acetylphenoxy)-N-[(2)-1-amino-4-methyl-1-oxo pentan-2-yl]-4,5-dihydroxycyclohexene-1-carboxamide and Ethyl 4-[5-methyl-2-oxo-10,20,50,60,70,70 a-hexahydro-1H-spiro[indole-3,30-pyrrolizine]-20-ylamido] benzoate. Molecular docking of those compounds with the a–glucosidase enzyme was performed to confirm their antidiabetic potential. These bioactive compounds could be suggested as a-glucosidase inhibitors and functional food additives